Absorptive Capacity, Innovation and Performance in Moroccan Small and Medium-sized Enterprises - BOUGADIR , Hanane; ZAHIR , Mustapha (Revue Internationale des Sciences de Gestion, 2025)
Given the scarcity of their resources, small and medium-sized enterprises (SMEs) are very sensitive to the effects of globalization and the rapid advancement of technology. Moreover, their internal knowledge is insufficient to enable them to achieve commercial performance, innovate, and survive. They must, therefore, imperatively seek external information. However, the development of dynamic capabilities and the capitalization on the opportunities offered within their environment to innovate, depend largely on their absorptive capacity. The objective of this article is to verify this postulate through empirical research using a qualitative approach based on a multiple case study. The aim is to examine how the five key components of absorptive capacity—recognition, acquisition, assimilation, transformation, and exploitation of knowledge— contributes to innovation, and therefore enhance performance, in the context of Moroccan SMEs. This study's findings can serve as a valuable resource for policymakers and organizations seeking to foster the growth and development of these enterprises. By identifying best practices and potential barriers to innovation, this research provides insights that can inform strategies for supporting SME success.